The sphinx : Franklin Roosevelt, the Isolationists, and the road to World War II - Wapshott, Nicholas (W.W. Norton & Company, 2015)
May 1938. Franklin Delano Roosevelt--recently reelected to a second term as president--contemplated two possibilities: the rule of fascism overseas, and a third term. With Hitler's reach extending into Austria, and with the atrocities of World War I still fresh in the American memory, Roosevelt faced the question that would prove one of the most defining in American history: whether to once again go to war in Europe. In this book, journalist Nicholas Wapshott recounts how an ambitious and resilient Roosevelt--nicknamed "the Sphinx" for his cunning, cryptic rapport with the press--devised and doggedly pursued a strategy to sway the American people to abandon isolationism and take up the mantle of the world's most powerful nation. Chief among Roosevelt's antagonists was his friend, stock market magnate Joseph P. Kennedy. Kennedy's interests aligned him with a war-weary American public, and he counted among his allies no less than Walt Disney, William Randolph Hearst, and Henry Ford--prominent businessmen who believed America had no business in conflicts across the Atlantic. The ensuing battle--waged with fiery rhetoric, agile diplomacy, media sabotage, and petty political antics--would land US troops in Europe within three years, secure Roosevelt's legacy, and set a standard for American military strategy for years to come.--From publisher description.